¿Inestabilidad o estabilidad en la política brasileña? Partidos políticos y presidente de la República contra la incertidumbre - Felisbino, Riberti de Almeida [UNESP] (My University, 2011)
This article examines what political scientists think of the Brazilian political system, especially in regard to the relationship between the executive and legislative branches. There are two opposing camps of scholars who focus on how political parties behave in the Chamber of Deputies. While the first defends a political system that produces undisciplined representatives, the second supports a legislative organization that produces disciplined politicians.
Instability or stability in Brazilian politics? Political parties and the presidency in the face of uncertainty
Keywords: Chamber of Deputies; Deputy; Legislative organization; Party leadership; Political parties